Circular economy strategies in supply chain management: an evaluation framework for airport operators - Sartzetaki, Maria; Karampini, Triantafyllia; Karagkouni, Aristi; Drimpetas, Evaggelos; Dimitriou, Dimitrios (Frontiers in Sustainability, 2025)
The transition from linear to circular economic systems represents a critical step towards achieving global sustainability goals. At the core of this transformation lies the development of supply chain management that needs to deviate from the traditional “take-make-dispose” approach to one focused on resource efficiency, waste reduction, and material recycling. The use of Business Intelligence (BI) technologies has great potential to support this shift through enhanced decision-making and operational efficiency. This study adopts an assessment framework drawing upon an extensive review of literature, empirical analysis, and case studies from various industries. A theoretical concept map was created to evaluate the application of circular economy principles to supply chain management, highlighting the role of business intelligence technology. The findings highlight how BI tools (such as advanced analytics, predictive modeling, and real-time monitoring) enable organizations to identify inefficiencies, streamline operations, and optimize resource usage across the supply chain. BI contributes to circular economy practices in areas such as product life cycle management, manufacturing, and reverse logistics by facilitating material tracking, recycling, and reintegration into the value chain. This study analyzes the relevance of strong technology infrastructure, facilitatory policy and regulatory arrangements, and collaboration between industries in the development of circular supply chain models. In addition, this study recommends capacity building initiatives that would enable organizations to acquire skills and capabilities to employ business intelligence-based strategies. Finally, the study provides recommendations to businesses, policy makers, and stakeholders on how business intelligence can support circularization. The proposed framework offers practical application and contributes to the body of literature relating to the incorporation of circular economy concepts into supply chain management.